Maqashid Syariah And Professional Zakat: A Critical Review Of Zakat Management Policy In Indonesia - Zihab Zihab; Ahmad Djalaluddin; Misbahul Munir; Said Abdelaal Abdelrahman Emam (JURNAL ECONOMINA, 2026)
This research critically examines the policy of professional zakat management in Indonesia through the analytical lens of maqashid al-shari'ah. This research employs a descriptive qualitative approach with a library research method, drawing data from statutory regulations, fatwas, and Scopus- and Sinta-indexed scientific articles published between 2019 and 2026. The findings indicate that professional zakat is conceptually aligned with the five dimensions of maqashid al-shari'ah, namely hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, and hifz al-mal, since the collection of zakat from professional income promotes the equitable distribution of welfare and the protection of the community's wealth. Nevertheless, the implementation of professional zakat management policy in Indonesia still faces fundamental challenges, including regulatory inconsistency among institutions, low compliance among civil servant and private professional muzaki, weak reporting and accountability systems, and the underdeveloped digitalization of zakat governance. This research recommends strengthening technical regulations on professional zakat, harmonizing Baznas and Amil Zakat Institutions, and reinforcing the maqashid al-shari'ah foundation in every zakat distribution and utilization policy.